Isolation of Oxyberberine and β-Sitosterol from Berberis lycium Royle Root Bark Extract and In Vitro Cytotoxicity against Liver and Lung Cancer Cell Lines - Anwar, Muhammad Asad (Evid Based Complement Alternat Med, 2020)
Berberis lycium Royle has been traditionally used to cure rheumatism, eye and ear diseases, malarial fever, diabetes, stomach disorders, and skin diseases. There is a least amount of data available on cytotoxic capacity of Berberis lycium from Pakistani origin, so on this basis, the present study was aimed to screen Berberis lycium root bark extracts for cytotoxicity against cancer cell lines and isolation of chemical constituents from the most cytotoxic extract. Initial screening of extracts was performed on HepG2 cells at 100 μg/mL for 72 hours of treatment by using an MTT assay. Active fractions were subjected to a series of column chromatographies for the isolation of cytotoxic compounds. Molecular structures were elucidated by using combined data from (1)H-NMR, (13)C-NMR, and ESI-MS graphs. Assessment of reduction in cell proliferation by isolated compounds was performed on three human cancer cell lines (SK-Hep-1, HepG2, and NCI-H1299). Both n-hexane and chloroform fractions were found active with percent cell viabilities of 8.41 ± 2.23 and 22.31 ± 9.11 in HepG2 cells compared with lupeol 35.43 ± 3.35 percent viability. A protoberberine alkaloid identified as oxyberberine was isolated from chloroform fraction while β-sitosterol was isolated from n-hexane fraction. Oxyberberine inhibited SK-Hep-1 cell proliferation under a dose-dependent manner with an IC(50) value of 34.26 ± 3.34 μM while HepG2 cells showed 50% inhibition at 62.96 ± 4.12 μM. β-Sitosterol showed reduction in cell viability in SK-Hep-1 cells and HepG2 cells with IC(50) values of 123.12 ± 3.51 μM and 140 ± 4.21 μM. This is the first report on the isolation of oxyberberine and β-sitosterol from Berberis lycium root bark and their cytotoxic evaluation against SK-Hep-1 and NCI-H1299 cells. The cytotoxic potential of Berberis lycium Royle extracts and isolated compounds is suggesting that it is a promising candidate for anticancer drug discovery.